Cost, prices, and profits : their cyclical relations - Hultgren, Thor.; Pech, Maude R. (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1965)
In this volume, the author treats the relations among costs, prices, and profits. He develops new quarterly indexes of the physical volume of sales and output in a number of manufacturing industries, independent of measures of input.
Includes index
occ 15/01/2019
Loans
Keywords: Costs, Industrial; Profit